Activation of bombesin receptor Subtype-3 by [D-Tyr6, β-Ala11, Phe13, Nle14]bombesin6-14 increased glucose uptake and lipogenesis in human and rat adipocytes. (15th October 2018) - Moreno-Villegas, Zaida; Martín-Duce, Antonio; Aparicio, César; Portal-Núñez, Sergio; Sanz, Raúl; Mantey, Samuel A.; Jensen, Robert T.; Lorenzo, Oscar; Egido, Jesús; González, Nieves
Abstract: BRS-3 has an important role in glucose homeostasis. Its expression was reduced in skeletal muscle from obese and/or diabetic patients, and BRS-3 KO-mice developed obesity. In this work, focused on rat/human adipose tissue, BRS-3 gene-expression was lower than normal-levels in hyperlipidemic, type-2-diabetic (T2D), and type-1-diabetic rats and also in obese (OB) and T2D patients. Moreover, BRS-3 protein levels were decreased in diabetic rat and in obese and diabetic human fat pieces; but neither mutation nor even polymorphism in the BRS-3-gene was found in OB or T2D patients. Interestingly, in rat and human adipocytes, without metabolic alterations, [D-Tyr 6, β-Ala 11, Phe 13, Nle 14 ]bombesin6-14 ―BRS-3-agonist―, as insulin, enhanced BRS-3 gene/protein expression, increased, PKB, p70s6K, MAPKs and p90RSK1 phosphorylation-levels, and induced a concentration-related stimulation of glucose transport, GLUT-4 membrane translocation and lipogenesis, exclusively mediated by BRS-3, and abolished by wortmannin, PD98059 or rapamacyn. These results confirm that BRS-3 and/or its agonist are a potential therapeutic tool for obesity/diabetes. Highlights: BRS-3 gene/protein expression is downregulated in OB and T2D human-rat fat tissue. BRS-3-Agonist as insulin enhanced BRS-3 mRNA/protein level in human-rat normal adipocytes. BRS-3-Agonist induced GLUT-4 translocation to plasma membrane. BRS-3-Agonist stimulated glucose transport/lipogenesis in human-rat normal adipocytes. PI3K/MAPKs be implicated. BRS-3-Agonist stimulation is exclusively mediated by BRS-3.